Carbon Nitride with Rationally Designed π‐Conjugated Structure for Bright Blue‐Violet Light‐Emitting Diodes. Issue 31 (15th June 2022) - He, Xingchen; Meng, Lingqiang; Liu, Yanliang; Zhang, Xue; Cheng, Ziqiang; Huang, Hao; He, Rui; Pan, Hao; Kang, Yihong; Li, Jia; Wang, Yiqing; Chu, Paul K.; et al.
Abstract: Carbon nitride consisting of the broken π‐conjugated structure (bc‐CN) is designed as the emitting layer in a blue‐violet light emitting diode (LED). The bc‐CN is prepared by a metal‐oxide (MgO) template‐assisted method, in which the low reaction temperature and nano MgO jointly control the degree of polymerization to form cyano groups and broken π‐conjugation in the bc‐CN nanosheets (bc‐CN NS) which emit intense blue‐violet photoluminescence at 412 nm. The broken π‐conjugated heptazine‐ring structure in the bc‐CN NS mitigates non‐radiation energy loss and promotes the d *–LP transition. As a result, a high quantum efficiency of 73.1% is achieved. The excellent dispersing ability of the bc‐CN NS enables solution‐based fabrication of the light emitting diode (LED). The LED exhibits intense electroluminescence of 236 cd m −2 at 412 nm with an external quantum efficiency of 0.46%. The broken π‐conjugation modulates the optical properties of the polymerized carbon nitride semiconductor giving rise to intense blue‐violet electroluminescence, which is very desirable for printable and wide‐color‐gamut display devices. Abstract : Carbon nitride with a broken π‐conjugated structure (bc‐CN) is synthesized by a nano‐template assisted polymerization method, both the intense bright blue‐violet photoluminescence and electroluminescence are achieved on the bc‐CN.